2021
DOI: 10.1175/mwr-d-21-0061.1
|View full text |Cite
|
Sign up to set email alerts
|

Microphysics Impacts on the Warm Conveyor Belt and Ridge Building of the NAWDEX IOP6 Cyclone

Abstract: This study investigates diabatic processes along the warm conveyor belt (WCB) of a deep extra-tropical cyclone observed of the North Atlantic Waveguide and Downstream Impact Experiment (NAWDEX). The aim is to investigate the effect of two different microphysics schemes, the one-moment scheme ICE3 and the quasi two-moment scheme LIMA, on the WCB and the ridge building downstream. ICE3 and LIMA also differ on the processes of vapor deposition on hydrometeors in cold and mixed-phase clouds. Latent heating in ICE3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…Display of the earth's surface and shadows place trajectories in spatial context. are sensitive to the cloud microphysical processes implemented in the numerical model, and may in turn, introduce uncertainties to WCB ascent (Joos and Forbes, 2016;Mazoyer et al, 2021). As the scale of cloud microphysical processes responsible for precipitation formation is too small to be explicitly resolved in NWP models, parameterizations are used to calculate the integrated effects on the resolved prognostic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Display of the earth's surface and shadows place trajectories in spatial context. are sensitive to the cloud microphysical processes implemented in the numerical model, and may in turn, introduce uncertainties to WCB ascent (Joos and Forbes, 2016;Mazoyer et al, 2021). As the scale of cloud microphysical processes responsible for precipitation formation is too small to be explicitly resolved in NWP models, parameterizations are used to calculate the integrated effects on the resolved prognostic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Embedded convective activity within WCBs was initially identified using airborne and satellite-derived data within an extratropical cyclone during the Experiment on Rapidly Intensifying Cyclones over the Atlantic (ERICA) field experiment (Neiman et al, 1993). Various ground-based, spaceborne and airborne remote sensing measurements confirm the regular presence of convective activity in the warm sector of extratropical cyclones and WCBs in particular (Crespo and Posselt, 2016;Flaounas et al, 2016Flaounas et al, , 2018Oertel et al, 2019;Blanchard et al, 2020;Jeyaratnam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Maddison et al (2019Maddison et al ( , 2020 showed that the low predictability of the block onset at medium range was associated with uncertainties in the timing, location and intensity of that cyclone. Blanchard et al (2020) and Blanchard et al (2021) studied the WCB-embedded convection by performing convection-permitting model simulations, while Mazoyer et al (2021) analysed the impact of cloud microphysics on the WCB activity of the Stalactite cyclone with similar convection-permitting simulations. Flack et al (2021) analysed the whole life cycle of the cyclone in simulations of two climate models.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty in the representation of latent heat released during cloud formation can represent a dominant source of initial error growth (Baumgart et al, 2019). In general, WCBs influence the large-scale flow through both direct PV modification in the lower and upper troposphere (e.g., Rossa et al, 2000;Pomroy and Thorpe, 2000;Joos and Forbes, 2016;Oertel et al, 2020;Mazoyer et al, 2021) and their related divergent outflow in the upper troposphere (e.g., Grams and Archambault, 2016;Steinfeld and Pfahl, 2019;Teubler and Riemer, 2021).…”
mentioning
confidence: 99%
“…The WCB ascent strength and its isentropic outflow level, which are tightly related to latent heat release, strongly impact the upper-level divergent wind field. It has been shown that uncertainty in the representation of latent heating substantially influences the WCB's cross-isentropic ascent strength (e.g., Martínez-Alvarado et al, 2014;Joos and Forbes, 2016;Mazoyer et al, 2021) and the frequency of WCB ascent (Pickl et al, 2022). A misrepresentation of WCB ascent, and its isentropic outflow level, can influence the jet stream wind speed (Schäfler and Harnisch, 2015) and also lead to forecast busts through underestimation of the downstream ridge amplitude (Grams et al, 2018).…”
mentioning
confidence: 99%